Eupterotegaeus ornatissimus - Murvanidze, Maka; Cilbircioğlu, Cihan; Özdemir, Esengül; Inak, Emre (Zenodo, 2020)
Published as part of Murvanidze, Maka, Cilbircioğlu, Cihan, Özdemir, Esengül & Inak, Emre, 2020, Checklist of oribatid mites (Acari: Oribatida) of the Central Black Sea basin of Turkey with new records for the country, pp. 255-277 in Persian Journal of Acarology 9 (3) on page 259, DOI: 10.22073/pja.v9i3.61909, http://zenodo.org/record/5236444

Eupterotegaeus ornatissimus (Berlese, 1908) Material – One specimen in Aluçdağı National Park, N 40° 49′ 75.37′′, E 32° 58′ 26.46′′, alt. = 1402 m, 15 July 2018, soil. Previous record in Turkey – Sakarya (Susyal et al. 2018). Global distribution – Holarctic. Ecology – Forest soils.
Keywords: Compactozetidae; Arthropoda; Arachnida; Eupterotegaeus ornatissimus; Animalia; Biodiversity; Sarcoptiformes; Eupterotegaeus; Taxonomy; 15. Life on land